(untitled) (Heritage, 2024)
Тhe essential purpose of this scientific article is to point out the already existing cause-and-effect relation between security and economic policy in contemporary international relations, on the case study of the Open Balkans. The analysis is focused on foreign direct investments and on the current security challenges and risks faced by actors involved in the Open Balkans initiative. In other words, this paper shows a double cause-and-effect relation: on the one hand, how security circumstances on the ground affect the attraction of foreign direct investments, and economic development policies in general; on the other hand, how much economic development in general, and thus foreign direct investments, determine security challenges and risks and how actors of the Open Balkans face them. The conclusion is clear: economic policies, and the economic performances and prosperity of actors within the framework of the Open Balkans contribute to the improvement of the security situation within this initiative, above all when it comes to contemporary security challenges and risks.